Do Women Earn Less Even as Social Entrepreneurs? - Saul Estrin; Ute Stephan; Sunčica Vujić (Institute for the Study of Labor (IZA), 2014)
Based upon unique survey data collected using respondent driven sampling methods, we investigate whether there is a gender pay gap among social entrepreneurs in the UK. We find that women as social entrepreneurs earn 29% less than their male colleagues, above the average UK gender pay gap of 19%. We estimate the adjusted pay gap to be about 23% after controlling for a range of demographic, human capital and job characteristics, as well as personal preferences and values. These differences are hard to explain by discrimination since these CEOs set their own pay. Income may not be the only aim in an entrepreneurial career, so we also look at job satisfaction to proxy for non-monetary returns. We find female social entrepreneurs to be more satisfied with their job as a CEO of a social enterprise than their male counterparts. This result holds even when we control for the salary generated through the social enterprise. Our results extend research in labour economics on the gender pay gap as well as entrepreneurship research on women's entrepreneurship to the novel context of social enterprise. It provides the first evidence for a "contented female social entrepreneur" paradox.
Keywords: J28; J31; J71; L32; 330; social entrepreneur; gender pay gap; social enterprise; earnings; job satisfaction